2003
DOI: 10.1074/jbc.m209436200
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of TgVP1, a Type I Vacuolar H+-translocating Pyrophosphatase fromToxoplasma gondii

Abstract: Here we report the isolation and characterization of a type I vacuolar-type H ؉ -pyrophosphatase (V-PPase), TgVP1, from an apicomplexan, Toxoplasma gondii, a parasitic protist that is particularly amenable to molecular and genetic manipulation. The 816-amino acid TgVP1 polypeptide is 50% sequence-identical (65% similar) to the prototypical type I V-PPase from Arabidopsis thaliana, AVP1, and contains all the sequence motifs characteristic of this pump category. Unlike AVP1 and other known type I enzymes, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Surprisingly, our localization data revealed that P-gp was found not only on the plasma membrane of the parasite, but also in organelles morphologically resembling acidocalcisomes and labeled with the acidocalcisome marker VP1, further supporting a P-gp involvement in Ca 2+ regulation. Similarly to the observations with the acidocalcisome marker type I vacuolar-type H + -pyrophosphatase [51], P-gp transiently re-localized in a collar-like structure at the apical end of extracellular parasites. Thus, we can propose a model where P-gp may participate in the Ca 2+ homeostasis via facilitating Ca 2+ uptake in acidocalcisomes by contributing to the establishment of the proton gradient in the organelles and, in addition, via promoting the function of TgA1.…”
Section: Discussionsupporting
confidence: 73%
“…Surprisingly, our localization data revealed that P-gp was found not only on the plasma membrane of the parasite, but also in organelles morphologically resembling acidocalcisomes and labeled with the acidocalcisome marker VP1, further supporting a P-gp involvement in Ca 2+ regulation. Similarly to the observations with the acidocalcisome marker type I vacuolar-type H + -pyrophosphatase [51], P-gp transiently re-localized in a collar-like structure at the apical end of extracellular parasites. Thus, we can propose a model where P-gp may participate in the Ca 2+ homeostasis via facilitating Ca 2+ uptake in acidocalcisomes by contributing to the establishment of the proton gradient in the organelles and, in addition, via promoting the function of TgA1.…”
Section: Discussionsupporting
confidence: 73%
“…A vacuolar type H + -translocating pyrophosphatase (TgVP1) has been described in T. gondii and shown to localize to both the acidocalcisomes [36, 37] and the newly described PLV/VAC [14, 15]. Co-staining with antibodies against TgNHE3 and TgVP1 [14] indicated that TgNHE3 co-localizes with TgVP1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One is the vacuolartype H + -ATPase, a macromolecular complex of 14 subunits (Bowman et al, 2009; Lu et al, 1998; Marchesini et al, 2002; Rodrigues et al, 2000; Ruiz et al., 2001a; Yagisawa et al, 2009), and the other is the V-H + -PPase, a single subunit protein that uses PP i instead of ATP to transport protons (Drozdowicz et al, 2003; Rodrigues et al, 1999a; Ruiz et al, 2001a; Scott et al, 1998; Yagisawa et al, 2009). Only the gene for the T. cruzi V-H + -PPase could be functionally expressed in yeast (Hill et al, 2000).…”
Section: Acidocalcisomes In Protistsmentioning
confidence: 99%